The projectification of the public sector - Hodgson, Damian E.; Fred, Mats; Bailey, Simon; Hall, Patrik
In recent decades, we have witnessed an increasing use of projects and similar temporary modes of organising in the public sector of nations in Europe and around the world. While for some this is a welcome development which unlocks entrepreneurial zeal and renders public services more flexible and accountable, others argue that this seeks to depoliticise policy initiatives, rendering them increasingly technocratic, and that the project organisations formed in this process offer fragmented and unsustainable short-term solutions to long-term problems.